214 EVALUATION OF THE HEARING FOUNDATION OF CANADA SOUND SENSE NOISE-INDUCED HEARING LOSS PREVENTION PROGRAM. Issue 1 (1st January 2007) - Nabi, S. M.; Bryce, G.; Leiren, B.; Hannan, G.; Dharamsi, S.; Westerberg, B.
Abstract : Approximately 10% of people in North America have some level of hearing impairment. One-third of these may be due to excessive noise exposure, of which a significant proportion is due to recreational activities. In 2001, Niskar et al found that approximately 12.5% of children 6 to 19 years of age experienced some degree of permanent or temporary hearing loss. The economic burden is in the billions of dollars, and the long-term personal effects include social isolation, depression, and possible decreased academic and occupational performance. This study is designed to determine whether the short- and long-term acoustic risk-taking behaviors of sixth-grade children change in response to a hearing conservation education intervention program (Hearing Foundation of Canada's Sound Sense ). Method: Sixth-graders from the Vancouver School Board region and their legal guardians will be part of this study. The Vancouver School Board will randomly approach elementary schools in its region. Ten to 25 Vancouver School Board elementary schools will participate and will be exposed to a hearing conservation program. A control group of a similar number of schools not exposed to the program will be selected from those not assigned to the intervention group. The intervention group (children and legal guardians) will be exposed to the Hearing Foundation of Canada's Sound Sense youth noise-induced hearing loss prevention program in early November 2006. The children and legal guardians of the intervention group will receive self-administered surveys prior to the intervention program, 2 weeks after the intervention program, and 6 months after the intervention program prior to completion of the school year. The control group (children and legal guardians) will receive the same surveys at the same interval time points. The change in correct responses of the children and legal guardians from the pre- to postintervention questionnaire and the correct responses of the intervention group versus the control group at the same point in time over multiple time periods will all be used as primary efficacy indicators. Statistical analysis will consist of a question-question response comparison in an individual using repeated measures analysis, as well as a comparison of means between groups at each time point.